Extended cost-benefit analysis of holm oak dehesa multiple use and cereal-grass rotations - Martín, D.; Campos, P.; Cañellas, I.; Montero, G. (Forest Systems, 2001)
The historical formation of holm oak (Quercus ilex L.) dehesa woodlands has often resulted in either rapid deforestation episodes by means of clear cuts or slower depletion of oak woodlands due to tree natural mortality and the absence of tree natural regeneration. Consequently, holm oak woodlands have been progressively converted into rough pasturelands, cereal croplands and scrublands. Whilst this tendency of holm oak exhaustion was not socially questioned, scientists and conservationists defending oak woodland conservation providing long run economic and environmental arguments were regarded as romantics ignoring the necessity for social progress and development. Today, these romantics are perceived as nature conservation pioneers and many of their arguments and concepts have been included in science and politics. This paper shows that cereal cropping and permanent grassland uses are more profitable to Extremadura’s landowners than holm oak artificial plantations and monitored holm oak natural regeneration. Increasing social demand for recreational and conservation services have been taken into account by Spanish and European public authorities. Along last decade, the European Union and the Spanish government have financed oak reforestation over extensive-use croplands of West and Southwest Spain, resulting in an unprecedented net increase in holm oak woodlands. The presented extended cost-benefit analysis shows that even after incorporating estimated income derived from public and private consumption of environmental services, uses associated to treeless cropland, pastureland and scrubland are still preferred to traditional extensive multiple use associated to dehesa holm oak woodlands.